Aortic Valve Involvement in a Patient With Granulomatosis With Polyangiitis - Gurmeet SINGH,; Surinder Kumar BALI,; Varsha KOUL1, (Archives of Rheumatology, 2014)
Cardiac involvement in granulomatosis with polyangiitis is rare. In this article, we describe a 47-year-old male case of aortic valve involvement with granulomatosis with polyangiitis. The patient had multi-system involvement in the form of pulmonary, renal, cutaneous involvement along with high levels of anti-proteinase 3. Echocardiography revealed a mass over the anterior leaflet of aortic valve with a mild aortic stenosis and aortic regurgitation. We suggest that clinicians should perform a thorough cardiac examination for any possible valvular involvement in patients with granulomatosis with polyangiitis.